Adherence to Intravenous Chemotherapy in African American and White Women With Early-Stage Breast Cancer. Issue 2 (March 2015) - Wells, Jessica S.; Strickland, Ora L.; Dalton, Jo Ann; Freeman, Sarah
Abstract : Background: Adherence to intravenous chemotherapy offers survival and recurrence-free benefits for women diagnosed with early-stage breast cancer. However, previous studies have found that African American women are more likely to discontinue intravenous chemotherapy early, thus shortening their survival. Yet the existence of racial differences and predictors of adherence to chemotherapy treatment between African American and white women are largely understudied or inconsistent. Objective: The purposes of this study were to examine factors that influence the decision to adhere to chemotherapy in African American and white women diagnosed with early-stage breast cancer and to test for racial differences that may exist in this sample. Interventions/Methods: The study recruited a convenience sample of 99 African American and white women. Factors examined were sociodemographic variables (age, race, access to healthcare), social support, religious coping, chemotherapy adverse effects, depression, breast cancer knowledge, health beliefs, cancer fatalism, and days from diagnosis to treatment. Data analyses included logistic regression modeling. Results: No racial differences in adherence to intravenous chemotherapy between African American and white women were found ( χ 2 = 2.627, P = .10). Days to treatment (odds ratio [OR], 0.982, P = .058), health insurance (OR, 0.121; P = .016), change in depression (OR, 0.935; P = .118), and symptom severity (OR, 0.950; P = .038) were independently associated with nonadherence to chemotherapy. Conclusions: This study provides emerging evidence of factors that may be potentially modified with interventions at the clinical setting. Implications for Practice: The findings can be used to spearhead future intervention studies that improve treatment decision making to chemotherapy adherence.